Mutant DD genotype of NFKB1 gene is associated with the susceptibility and severity of coronary artery disease. (February 2017) - Luo, Jun-Yi; Li, Xiao-Mei; Zhou, Yun; Zhao, Qiang; Chen, Bang-Dang; Liu, Fen; Chen, Xiao-cui; Zheng, Hong; Ma, Yi-Tong; Gao, Xiao-Ming; Yang, Yi-Ning
Abstract: Nuclear factor κappa B (NF-κB) is an important transcription factor in the development and progression of coronary artery disease (CAD). Recent evidence suggests that -94 ATTG ins/del mutant in the promoter of NFKB1 gene is an essential functional mutant. The present study demonstrated the frequencies of the del/del (DD) genotype and del (D) allele were significantly higher in CAD patients than in controls. CAD patients carrying mutant DD genotype had worse stenosis of diseased coronary arteries compared to those carrying ins/ins (II) or ins/del (ID) genotype. Plasma levels of endothelial nitric oxide synthase (eNOS) were lower, while inflammatory cytokine incnterlukin-6 (IL-6) was higher in CAD patients with DD genotype than those with II or ID genotype (both P  < 0.05). In vitro study showed that mutant human umbilical vein endothelial cells (DD genotype HUVECs) were more susceptible to H2 O2 -induced apoptosis, which was accompanied with a decreased Bcl-2 expression. Further, mutant HUVECs had lower eNOS but higher IL-6 mRNA levels and decreased phosphorylation of eNOS under H2 O2 -stimulation (both P  < 0.05). Compared to wild type cells (II genotype), significantly downregulated protein expression of total NF-κB p50 subunit were observed in mutant HUVECs with or without oxidative stress, and a lower expression of unclear p50 was associated with a decreased p50 nuclear translocation in mutant HUVECs versus wild type cells under H2 O2 -stimulation (both P  < 0.05). In conclusion, mutant DD genotype of NFKB1 gene is associated with the risk and severity of CAD. Dwonregulation of NF-κB p50 subunit leads to exacerbated endothelial dysfunction and apoptosis and enhanced inflammatory response that is the potential underlying mechanism. Highlights: Association between NFKB1 gene mutant DD and the risk/severity of CAD A close link of this mutant to endothelial dysfunction and higher inflammatory status Mechanism related to decreased NF-kB p50 expression and nuclear translocation